Effect of extremely low frequency electromagnetic fields on growth rate and morphology of bacteria - ÖZAYDIN, AYŞE NİLÜFER; AKAKIN, DİLEK; GARİP, GÜNSELİ AYŞE; AKSU, MEHMET BURAK (TAYLOR & FRANCIS LTD, 2011)
Purpose: To determine the effect of extremely low frequency (<300 Hz) electromagnetic fields (ELF-EMF) on the growth rate of Gram-positive and Gram-negative bacteria and to determine any morphological changes that might have been caused by ELF-EMF. Materials and methods: Six bacterial strains, three Gram-negative and three Gram-positive were subjected to 50 Hz, 0.5 mT ELF-EMF for 6 h. To determine growth rate after ELF-EMF application, bacteria exposed to ELF-EMF for 3 h were collected, transferred to fresh medium and cultured without field application for another 4 h. Growth-rate was determined by optical density (OD) measurements made every hour. Morphological changes were determined with Transmission electron microscopy (TEM) for two gram-negative and two gram-positive strains collected after 3 h of field application. Results: A decrease in growth rate with respect to control samples was observed for all strains during ELF-EMF application. The decrease in growth-rate continued when exposed bacteria were cultured without field application. Significant ultrastructural changes were observed in all bacterial strains, which were seen to resemble the alterations caused by cationic peptides. Conclusion: This study shows that ELF-EMF induces a decrease in growth rate and morphological changes for both Gram-negative and Gram-positive bacteria.
Keywords: ELF-EMF; bacterial growth rate; morphological changes; TEM; PULSED ELECTRIC-FIELDS; ESCHERICHIA-COLI; MAGNETIC-FIELD; STAPHYLOCOCCUS-AUREUS; EXPOSURE; CELLS; CANCER